2015
DOI: 10.4136/ambi-agua.1573
|View full text |Cite
|
Sign up to set email alerts
|

Agregação do solo, carbono orgânico e emissão de CO2 em áreas sob diferentes usos no Cerrado, região do Triângulo Mineiro

Abstract: Soil aggregation and carbon distribution are important indicators of soil quality. Moreover, these attributes are closely related to CO 2 fluxes in the soil-atmosphere interface. We sought to evaluate soil aggregation, organic carbon distribution and CO 2 evolution in different land uses of Minas Gerais Triangle. Four different land uses were selected: (1) Panicum maximum, (2) Panicum maximum Jacqvr. (Tanzânia), (3) sugarcane, and (4) native Cerrado (control). In each land-use type, soil samples from a 0-10 cm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 26 publications
0
9
0
1
Order By: Relevance
“…In both fragments studied, CMI values lower than the reference area were observed in the surrounding NTS areas (Table 5). These results demonstrate that the modification caused by the conversion of natural areas may compromise soil quality (Rosset et al, 2019b), mainly in surface layers, affecting the quality of SOM due to the low diversity of species in the soybean/corn succession over the years of cultivation, which directly influences the physical quality (Sales et al, 2018), chemistry (Souza et al, 2018) and the biological activity (Borges et al, 2016) of the soil over the years of cultivation.…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…In both fragments studied, CMI values lower than the reference area were observed in the surrounding NTS areas (Table 5). These results demonstrate that the modification caused by the conversion of natural areas may compromise soil quality (Rosset et al, 2019b), mainly in surface layers, affecting the quality of SOM due to the low diversity of species in the soybean/corn succession over the years of cultivation, which directly influences the physical quality (Sales et al, 2018), chemistry (Souza et al, 2018) and the biological activity (Borges et al, 2016) of the soil over the years of cultivation.…”
Section: Resultsmentioning
confidence: 84%
“…Thus, physical granulometric fractionation of SOM, which quantifies labile and recalcitrant fractions, is an important environmental assessment tool (Rosset et al, 2019b). In addition to the forms of fractionation, the evaluation of soil mineralizable carbon is another variable that contributes to evaluate soil biological quality (Borges et al, 2016;Rosset et al, 2019a), through the emission of CO2, product of the activity of microorganisms that decompose SOM (Rosset et al, 2019b).…”
Section: Introductionmentioning
confidence: 99%
“…High SOC content in the HU fraction are usually found in soils with application of organic soil fertilizers. Borges et al (2015) found that soils treated with PS and poultry litter had higher SOC in the HU fraction than those with mineral fertilizer or without fertilizer application. The compounds that constitute this fraction are more stable, they present higher resistance to biodegradation (Guerra et al, 2008).…”
Section: Resultsmentioning
confidence: 92%
“…The SOM was fractionated by determining the SOC content in the fractions fulvic acids (FA), humic acids (HA), and humin (HU), according to the methodology described by Benites et al (2003).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation